1999
DOI: 10.1182/blood.v94.6.2090
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Epstein-Barr Virus-Like Virus, HVMNE, in aMacaca Nemestrina With Mycosis Fungoides

Abstract: Epstein-Barr virus (EBV) infection of humans has been associated with the development of lymphoid malignancies mainly of B-cell lineage, although occasionally T-cell lymphomas have been reported. We describe here the characterization of a novel EBV-like virus (HVMNE) isolated from a simian T-cell lymphotropic virus type I/II (STLV-I/II) seronegative pigtailed macaque (Macaca nemestrina) with a cutaneous T-cell lymphoma. Immunohistochemistry studies on the skin lesions demonstrated that the infiltrating cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The same DNA fragment was found also in two CD8+ T-cell lines established from this tumor. Sequencing analysis of this fragment revealed 90% sequence identity with EBV DNA polymerase, and phylogenetic analysis indicated a distinct virus (HV MNE ) of the LCV genus [84]. Furthermore, herpesvirus-like particles were demonstrated by electron microscopy in the two T-cell lines [84].…”
Section: Ebv-associated T/nk-cell Lymphoproliferative Diseasesmentioning
confidence: 93%
See 2 more Smart Citations
“…The same DNA fragment was found also in two CD8+ T-cell lines established from this tumor. Sequencing analysis of this fragment revealed 90% sequence identity with EBV DNA polymerase, and phylogenetic analysis indicated a distinct virus (HV MNE ) of the LCV genus [84]. Furthermore, herpesvirus-like particles were demonstrated by electron microscopy in the two T-cell lines [84].…”
Section: Ebv-associated T/nk-cell Lymphoproliferative Diseasesmentioning
confidence: 93%
“…Sequencing analysis of this fragment revealed 90% sequence identity with EBV DNA polymerase, and phylogenetic analysis indicated a distinct virus (HV MNE ) of the LCV genus [84]. Furthermore, herpesvirus-like particles were demonstrated by electron microscopy in the two T-cell lines [84]. Subsequent studies showed that HV MNE transformed rabbit T cells and induced T-cell lymphoma in rabbits [85].…”
Section: Ebv-associated T/nk-cell Lymphoproliferative Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…Experimental infection of macaques with RLCV and RRV have been used as models for AIDS-associated malignancies caused by gammaherpesviruses [ 9 13 ]. In addition, a related virus isolated from pig tailed macaques with lymphoma was shown to cause lymphoma in rabbits[ 14 , 15 ]. However, the role of naturally occurring gammaherpesvirus infections in macaques subsequently infected experimentally with SIV/SHIV and their role in malignancies has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…EBV-like viruses in closely related primates have been recognized for over 25 years including Herpesvirus gorilla ( Pongine herpesvirus 3 ) (Neubauer et al ., 1979 ), Herpesvirus pan ( Pongine herpesvirus 1 ) (Gerber et al , 1976 ; Landon et al ., 1968 ), Herpesvirus pongo ( Pongine herpesvirus 2 ) (Rabin et al , 1978 ) and Herpesvirus papio ( Cercopithecine herpesvirus 12 ) (Falk et al ., 1976 , 1977 ), all belonging to the lymphocryptovirus subgroup of the gammaherpesvirus subfamily. More recently, lymphocryptoviruses have been identified in lymphoid tumours of several macaque species including cynomolgus macaque ( Macaca fascicularis ) (Hayashi et al ., 1995 , 1999 ; Li et al ., 1994 ), stump-tailed macaque ( Macaca arctoides ) (Wutzler et al ., 1995 ), pig-tailed macaque ( Macaca nemestrina ) (Rivadeneira et al ., 1999 ) and rhesus macaque ( Macaca mulatta ) (Moghaddam et al ., 1997 , 1998 ; Rangan et al ., 1986 ; Rivailler et al ., 2002 ). Various models for EBV-related lymphoid disease and infection have been developed from these findings.…”
Section: Introductionmentioning
confidence: 99%